Experiential Knowledge and Costs in the Internationalization Process - Eriksson, Kent; Johanson, Jan; Majkgård, Anders; Sharma, D. Deo (Journal of International Business Studies, 1997)
Using a behavioral approach, this study identifies and delineates components of experiential knowledge in the internationalization process. Three hypotheses are developed and tested. They center around the lack of knowledge in the areas of foreign business, foreign institutions and firm internationalization, as well as the effect that this lack of knowledge has on managers' perceived cost in the internationalization process. With the help of a LISREL-based structural model, the three hypotheses are tested on a sample of 362 service firms. The analysis shows that lack of internationalization knowledge has a strong impact on the lack of both business and institutionalization. But there is no direct effect of lack of internationalization knowledge on perceived cost of internationalization.